PERANCANGAN SISTEM INFORMASI PENYIMPANAN REKAM MEDIS RAWAT JALAN DI UPTD PUSKESMAS - Sunarmi; Yuda Syahidin; Yuyun Yunengsih (INFOKES (Informasi Kesehatan), 2021)
The research aims to produce a system of record-keeping information in Visual Studio 2010 at UPTD Puskesmas. Software development methodology used waterfall system. The research found several problems in the processing of medical records storage in UPTD Puskesmas, namely : (1) Storage processing of outpatient medical records have been computerized, but the recording was still using Microsoft Excel so but that takes time was relatively long ; (2)Sometimes the data that has been entered inaccurate; (3)The duplication of data. The suggestion was given:: (1). Training and understanding of the clerk in the process and operate the report; (2). Information system is easy to creating operate so that the officers have that has been processed from Microsoft Excel but to make a report with the data has been processed. Keywords: Design ,Information Systems, Filling, Medical record.